Pengaruh Academic Grit dan Environmental Stressor terhadap Cognitive Functioning pada Pelajar Pengkaji Kitab Al-Jurumiyah di Indonesia - Saputra, Aqmal Maulana; Sultoni, Muhamad Ikbal; Hakim, Danar Hadi Khoerul; Fadhlillah, Muhammad Syauqi; Hakim, Ilmi (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to examine the effect of academic grit (AG) and environmental stressors (ES) on cognitive functioning (CF) in Indonesian students studying the Al-Jurumiyah book. This study is important because studying a classic book like Al-Jurumiyah requires high cognitive abilities, but there has been no study that analyzes the predictor factors that influence it simultaneously.Method – This research employs a quantitative approach with regression design using a sample of 17 students in Bandung Regency (accidental sampling). Data was collected through adapted questionnaires: Academic Grit Scale (9 items, ?=0.70), Perceived Stress Scale (25 items, ?=0.87), and Cognitive Functioning Self-Assessment Scale (18 items, ?=0.84. The analysis included classical assumption tests and multiple regression with JASP 0.18. Findings – Multiple regression analysis showed that academic grit (AG) and environmental stressors (ES) explained 48.6% of the variance in cognitive functioning (CF) (adjusted R² = 0.486). The model was significant (F = 0.004) simultaneously. Partially, only AG had a significant positive effect on CF (? = 1.649; p = 0.009), while ES had a negative but insignificant effect (? = -0.050; p = 0.789). Research Implications – Practical implications of this study suggest the importance of strengthening non-cognitive aspects such as grit and motivation, especially in memorization-based and syntactic analysis-based curricula. Interventions such as self-regulation training and effective learning strategies may enhance cognitive functioning. Although the effects of environmental stressors (ES) were not significant, the negative trend suggests the need for supportive and low-pressure learning environments. The limitations of correlational and cross-sectional designs limit causal inference and temporal analysis.